Synthesis of nanosized metal particles from an aerosol - Stopić, Srećko R. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The synthesis of metallic nanoparticles from the precursor solution of salts using the ultrasonic spray pyrolysis method was considered in this work. During the control of process parameters (surface tension and density, the concentration of solution, residence time of aerosol in the reactor, presence of additives, gas flow rate, decomposition temperature of aerosol, type of precursor and working atmosphere) it is possible to guide the process in order to obtain powders with such a morphology which satisfies more complex requirements for the desired properties of advanced engineering materials.  Significant advance in the improvement of powder characteristics (lower particles sizes, better spheroidity, higher surface area) was obtained by the application of the ultrasonic generator for the preparation of aerosols. Ultrasonic spray pyrolysis is performed by the action of a powerful source of ultrasound on the corresponding precursor solution forming the aerosol with a constant droplet size, which depends on the characteristics of liquid and the frequency of ultrasound. The produced aerosols were transported into the hot reactor, which enables the reaction to occur in a very small volume of a particle and formation of  nanosized powder. Spherical, nanosized particles of metals (Cu, Ag, Au, Co) were produced with new and improved physical and chemical characteristics at the IME, RWTH Aachen University. The high costs associated with small quantities of produced nanosized particles represent a limitation of the USP-method. Therefore, scale up of the ultrasonic spray pyrolysis was performed as a final target in the synthesis of nanosized powder.
Keywords: MMCT transition; spray; ultrasound; nanoparticles; pyrolysis; aerosols